Structure of Communicative Competence of a Personality - Tur, Oksana (Pedagogical Discourse, 2016)
In this article, the definition is given to the concept «communicative competence» as integrative personal education which is shown in the process of communication as the ability to staticize and make use of previous experience of communicative activity. The main attention is focused on various options of the structure of communicative competence of the personality which have been offered in scientific psychology and pedagogical literature by many domestic and foreign scientists. On the basis of using theoretical methods in studying of given problem, two directions are allocated in classification of the component structure of communicative competence: some scientists represent structure of communicative competence by the description of the corresponding knowledge, abilities, skills, personal qualities, experience of communicative activity, the emotional attitude towards it; other scientists in the structure of communicative competence mark out different competences. In this article, are considered in details such concepts as: communicative knowledge (knowledge of native and foreign languages, etiquette rules of conduct, nonverbal means of communication); communicative abilities (ways of communicative actions performance, for example: ability to assess a communicative situation, to make the decision, to plan communicative actions); communicative skills (practical knowledge, experience of communicative activity). On the basis of analysis of scientific literature in this article are allocated the main components of communicative competence as: Gnostic (knowledge of features of communication); emotional (experience of communication, positive attitude towards people); individual (assessment of the personality), control, motivational and others. In this article has been made the conclusions that communicative competence formed in the process of acquisition of social and communicative experience. The author has offered the variant of structure of communicative competence which contains communicative, cross-cultural, social and information, social and political competences. The important component is personal and individual qualities of the person. Key words: communicative competence, structure, competences, cross-cultural communication, knowledge, abilities, skills, communication.